The Challenges Facing the South African Labour Movement: Mobilization of Diverse Constituencies in a Changing Context - Wood, Geoffrey; Dibben, Pauline (Relations industrielles / Industrial Relations, 2008)
There is a growing body of literature on the role and impact of unions in the developing world, and on their ability to mobilize members against a background of neo-liberal reforms. The South African trade union movement represents a source of inspiration to organized labour worldwide, but has faced many challenges over the years. This article engages with debates on union solidarity and worker democracy, and draws on the findings of a nationwide survey of members of the Congress of South African Trade Unions (COSATU) to explore the extent of fragmentation according to gender, age, skill level and ethnicity. The survey reveals regular participation in union affairs, democratic accountability, participation in collective action, and a strong commitment to the labour movement, but variation in levels of engagement between categories of union members indicates significant implications for union policy and practice.